Biology and development of xanthopimpla pedator (hymenoptera: ichneumonidae): pupal endoparasitoid of antheraea mylitta (Lepidoptera: Saturniidae) - Gathalkar, Ganesh B.; Barsagade, Deepak D.; Sen, Avalokiteswar (Annals of the Entomological Society of America, 2017)
The Antheraea mylitta (Drury) (Lepidoptera: Saturniidae) is a commercially important species for the production of tasar silk. However, the Xanthopimpla pedator (F.) (Hymenoptera: Ichneumonidae) is a major pupal endoparasitoid of A. mylitta, which affects the total tasar silk production in India. A gravid female X. pedator parasitizes the pupae of A. mylitta by depositing an egg, which produces a single offspring per host. We studied the development of immature forms of X. pedator by dissecting parasitized pupae of A. mylitta under laboratory conditions at 28-30 degrees C and 40-60% relative humidity. All immature stages of the parasitoid develop within the host in 20-22 d, by devouring the entire pupal content, resulting in dead or seedless cocoons. The total life cycle of X. pedator is completed inside the host pupa and the adult emerges out by rupturing the peduncle end of the cocoon. During development of X. pedator, five preimaginal stages, viz., egg, larval instars, prepupa, pupa, and a pharate adult, were observed. Xanthopimpla pedator passes through five larval instars identified by structural and morphometric variations. These include primary larva (L1), the intermediate larvae (L2-L4), and the finalinstar larva (L5). Biometric study and larval head width permitted the morphological separation of all five larval instars. In the present study, the biology and development of X. pedator inside the pupa of A. mylitta are reported for the first time with detailed photomicrographs. Therefore, the study may enable the information concerning physiological interactions between A. mylitta and its endoparasitoid, X. pedator.

Morphological characteristics of antennal microstructure and its ecological significance in xanthopimpla pedator (hymenoptera: ichneumonidae: pimplinae): insights into cocoon-concealed host detection - Gathalkar, Ganesh B.; Sharma, V. Pooja; Barsagade, Deepak D. (Microscopy and Microanalysis, 2026)
Xanthopimpla pedator (Fabricius) (Hymenoptera: Ichneumonidae: Pimplinae) is a specialist solitary pupal endoparasitoid of the tropical Tasar silkworm, Antheraea mylitta (Drury) (Lepidoptera: Saturniidae), causing significant ecological and economic losses each year. Female oviposits into cocoon-concealed pupae of A. mylitta, where the developing larva consumes the host, ultimately killing it. During host searching, females rely on their antennae as the principal sensory organs to detect and evaluate host suitability, although sensory structures on the ovipositor may also contribute to oviposition decisions. Scanning electron microscopy (SEM) revealed nine distinct microstructure/sensilla types: trichodea, basiconica, chaetica, placodea, grooved peg sensilla, campaniformia, microtrichia, B & ouml;hm's bristles, and glandular pores, including their respective subtypes. Additional microstructures, such as apical pegs, cuticular pores, and cuticular folds, were also observed. Sensilla trichodea were most abundant, followed by placodea, chaetica, and basiconica. Apical pegs at the antennal apex in both sexes are hypothesized to function in vibrational sounding during antennal tapping. Minimal sexual dimorphism in antennal sensilla was observed, limited to antennal length and flagellomere counts. These antennal features, including chemosensory and mechanosensory sensilla, are likely essential for host detection, discrimination, and oviposition, providing insights that could inform the development of semiochemical-based pest management tactics.
Keywords: antennal sensilla; endoparasitoid; host detection; scanning electron microscopy; tasar silkworm; ultrastructure